Literacy in a digital world the evolution and development of literacy proficiency - Dagostino, Lorraine 1947-; Bauer, Jennifer 1975-; Ryan, Kathleen (Professor) (Lanham, Maryland Rowman & Littlefield, 2024)
"The digital revolution has greatly influenced communication, meaning a current, analytical examination of changing literacy skills is needed. Becoming literate in today's world requires an understanding of traditional and electronic messaging venues in order for communications to not be misled by unrecognized influences. This book examines changes in the concept of literacy, including, the specific characteristics of evaluation literacy, predictors of literacy efficiency, the nature of audiences and users, and ethical concerns. It also examines the implications and applications for instruction, assessment, and professional development." --
Includes bibliographical references (pages 135-143).
Keywords: Information literacy; Technological literacy; Literacy -- History; Literacy -- Social aspects; Culture technologique